Method for improving conductivity of high-phosphorus copper alloy strip

By optimizing the composition and processing technology of high-phosphorus copper alloy, the conductivity of high-phosphorus copper alloy strips is improved, the problem of insufficient conductivity of existing materials is solved, and the consideration of high conductivity and strength is achieved.

CN119800252APending Publication Date: 2025-04-11CHINALCO LUOYANG COPPER PROCESSING CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510029816.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-08
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

The current high-phosphorus copper alloy strips have insufficient conductivity and cannot meet the needs of high-conductive applications.

Method used

By optimizing the composition and processing technology of high-phosphorus copper alloys, including adjusting the proportion of Cu, P, Fe and other elements during batching, using a cover annealing furnace for heat treatment and annealing, combined with semi-continuous casting, hot rolling and finishing rolling, the conductivity of the material is improved.

Benefits of technology

The conductivity of high-phosphorus copper alloy strips has been improved, stably reaching 83% IACS or above, meeting the requirements of high-conductive applications, while ensuring the strength and welding capabilities of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119800252A_ABST
    Figure CN119800252A_ABST
Patent Text Reader

Abstract

The invention provides a method for improving the electric conductivity of a phosphorus copper alloy strip. The method mainly comprises the steps of burdening, smelting, casting, saw cutting, heating, hot rolling, face milling, rough rolling, edge cutting, heat treatment annealing, cleaning and finished product finish rolling. Wherein in the burdening process, components including, by mass percent, more than or equal to 99.90% of Cu, 0.02-0.03% of P, 0.002-0.01% of Fe, less than or equal to 0.001% of Bi, less than or equal to 0.002% of Sb, less than or equal to 0.002% of As, less than or equal to 0.005% of Pb and less than or equal to 0.005% of S are adopted for proportioning; and during heat treatment annealing, horizontally placing in a cover type annealing furnace, and annealing at the temperature of 280-380 DEG C for 6-10 hours. The preparation technology of the high-phosphorus copper alloy is researched, the conductivity of the high-phosphorus copper alloy is improved under the condition that the material strength is guaranteed, and the use requirement of the high-phosphorus copper alloy in the power transmission and transformation market is met.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of copper alloy smelting and processing, and in particular to a method for improving the electrical conductivity of a phosphor copper alloy strip. Background Art

[0002] In recent years, with the rapid development of the power transmission and transformation industry and the solar photovoltaic industry, the demand for high-phosphorus copper alloys has been growing. These industries have extremely high requirements for the electrical conductivity, thermal conductivity, formability, surface quality and edge quality of copper materials. In the manufacture of high-end new transformers and solar cell modules, higher requirements are placed on the performance of the conductive raw materials used - copper strip products. For example, the copper strips in solar cell modules must have high electrical conductivity. Due to its advantages of higher strength and lower cost, high-phosphorus copper alloys have quickly replaced some high-cost pure copper in the power transmission and transformation market such as transformers, becoming one of the hottest materials in the copper alloy series. The national standard specifies that the electrical conductivity of high-phosphorus copper alloys is 75% IACS, which is far lower than that of red copper materials and cannot meet the use requirements of copper strips for high electrical conductivity purposes.

[0003] In view of the above reasons, it is necessary to design a method to improve the conductivity of high phosphorus copper alloy strip. Summary of the invention

[0004] In order to address the deficiencies in the prior art, the present invention provides a method for improving the electrical conductivity of a phosphor-copper alloy strip, studies the preparation process of a high-phosphor-copper alloy, and improves its electrical conductivity while ensuring material strength to meet the requirements for use in the power transmission and transformation market.

[0005] In order to achieve the above object, the specific scheme adopted by the present invention is: A method for improving the conductivity of a phosphor copper alloy strip, mainly comprising the steps of batching, smelting, casting, sawing, heating, hot rolling, milling, rough rolling, trimming, heat treatment annealing, cleaning, and finished product finishing; Wherein, when mixing the ingredients, by mass percentage, the ingredients of Cu≥99.90%, P 0.02-0.03%, Fe 0.002-0.01%, Bi≤0.001%, Sb≤0.002%, As≤0.002%, Pb≤0.005%, and S≤0.005% are used for mixing; During heat treatment annealing, place it flat in a bell-type annealing furnace and anneal at 280-380°C for 6-10 hours.

[0006] Furthermore, the total mass percentage of Bi, Sb, As, Pb and S does not exceed 0.03%.

[0007] Furthermore, the P element is added in the form of copper-phosphorus alloy, and the Fe element is added in the form of iron sheet.

[0008] Furthermore, during smelting, the prepared raw materials are put into a smelting furnace and covered with a mixture of graphite powder and dehydrated charcoal. The smelting temperature is 1120~1280℃. After smelting, the raw materials are allowed to stand to facilitate the floating of slag of oxides, sulfides and carbides in the melt. The floating slag is removed to purify the melt.

[0009] Furthermore, a semi-continuous casting machine is used for vibration casting to obtain an ingot, the casting speed is 4.0-10.0 m / h; the cooling water flow rate is 300-1200 l / min; during casting, an appropriate amount of borax or carbon black is used to cover the melt in the crystallizer.

[0010] Furthermore, before hot rolling, the ingot is heated by a walking beam heating furnace at a heating temperature of 800-950°C.

[0011] Furthermore, the ingot is hot rolled on the hot rolling equipment, the total processing rate of the hot rolled strip is ≥90%, online quenching and cooling is carried out, and water spray quenching and cooling is carried out on the hot rolling roller during the final hot rolling.

[0012] Furthermore, the electrical conductivity of the phosphor copper alloy strip is greater than 83% IACS.

[0013] Beneficial effects: (1) Compared with the existing phosphorus-containing copper alloys, the present invention designs a new high-phosphorus copper alloy through innovative optimization. The alloy narrows the range of phosphorus content in the high-phosphorus copper alloy strip by optimizing the components, and more accurately meets the performance requirements of the high-phosphorus copper alloy strip. At the same time, a small amount of iron is added to ensure the welding ability of the high-phosphorus copper alloy while forming a second phase with phosphorus, purifying the body and improving the conductivity of the material.

[0014] (2) According to the composition characteristics of high-phosphorus copper alloy that are different from ordinary copper, the present invention adopts a bell-type annealing furnace instead of a traditional air cushion annealing furnace for material annealing. Compared with air cushion annealing, bell-type annealing has a lower temperature and a longer time. Phosphorus and iron, as weakened aging alloys, are more sensitive to aging temperature. The annealing temperature of the material is appropriately reduced, and the material temperature is controlled between 280-380°C. The insulation time of the material is extended, so that the second phase has sufficient time to precipitate, the copper matrix is ​​purer, and the conductivity is higher. The composition ratio used in the present invention not only meets the composition requirements of the high-phosphorus alloy, but also improves the conductivity by more than 8% IACS on the original basis.

[0015] (3) After adopting the new processing technology, the conductivity of high-phosphorus copper alloy strip is stabilized at above 83% IACS, which is suitable for mass production. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] Figure 1The figure is a process flow chart of the method for improving the electrical conductivity of phosphorus copper alloy strip in the present invention. DETAILED DESCRIPTION

[0017] The technical solution of the present invention will be clearly and completely described below in conjunction with specific embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0018] The present invention discloses a method for improving the electrical conductivity of a high-phosphorus copper alloy strip, wherein the high-phosphorus copper alloy strip comprises the following components by weight percentage: copper Cu≥99.90%, phosphorus P: 0.02-0.03%; iron Fe: 0.002-0.01%; bismuth Bi≤0.001%; ​​antimony Sb≤0.002%; arsenic As≤0.002%; lead Pb≤0.005%; sulfur S≤0.005%. It should be noted that the sum of the mass percentages of Bi, Sb, As, Pb, and S does not exceed 0.03%. When the sum of these impurity elements is higher than 0.02%, the electrical conductivity of the material will be reduced. The specific method for improving the electrical conductivity of a high-phosphorus copper alloy strip is described in detail below.

[0019] (1) Ingredients The proportions are made according to the following ingredients: copper Cu≥99.90%, phosphorus P 0.02-0.03%; iron Fe 0.002-0.01%; bismuth Bi≤0.001%; ​​antimony Sb≤0.002%; arsenic As≤0.002%; lead Pb≤0.005%; sulfur S≤0.005%. Standard cathode electrolytic copper and waste materials returned from processing are weighed and put into the smelting furnace respectively; phosphorus is an element that is easy to burn out. In order to prevent it from burning out during direct addition and causing unstable phosphorus content in the ingot, copper-phosphorus alloy is used instead of phosphorus to be added directly. Iron is added directly in the form of iron sheets to control the iron and phosphorus content in the material, and to prevent the formation of a solid solution phase dissolved in the copper body during the processing heat treatment process due to excessive iron-phosphorus content, so that the proportion of copper in the matrix is ​​reduced, thereby reducing the overall conductivity of the material.

[0020] (2) Melting The weighed metals are mixed, and charcoal, graphite powder or graphite blocks are added. The furnace is filled with nitrogen or argon to smelt the metals into a melt at 1120~1280℃.

[0021] Take samples from the melt and analyze the content of the controlled components and the results of impurity control.

[0022] In order to ensure the quality of the melt, the raw materials and covering agents used must be dry. During the melting process, the inert gas filled into the furnace can facilitate the precipitation of gas in the melt, ensuring that the gas content in the melt is low.

[0023] After melting, it is necessary to let it stand for a while, which is conducive to the slag of some oxides, sulfides and carbides to float up. After floating up, the slag is removed to purify the melt.

[0024] After the melt is prepared, the composition is adjusted according to the sampling and analysis results; according to the burn-out of the elements, necessary trace elements are added to ensure that the composition is qualified.

[0025] (3) Casting When the composition is confirmed to be within the target range, casting begins.

[0026] When the copper liquid flows through the launder to the casting tube and flows into the crystallizer for casting, in order to prevent the elements in the launder from oxidizing, it can be covered with charcoal or graphite particles and protected by inert gas. Alternatively, the launder can be designed into a sealed structure and the length of the launder can be shortened.

[0027] The use of semi-continuous casting can be beneficial to ensuring the quality of ingots.

[0028] Vibration casting can be used in the casting process, which is conducive to the slag in the crystallizer floating up instead of entering the ingot.

[0029] During casting, an appropriate amount of borax, carbon black or protective gas is used to cover the melt in the crystallizer.

[0030] Casting speed: 4.0-10.0m / h; Cooling water flow: 300~1200l / min; Casting can be stopped when the ingot length required for strip is reached.

[0031] (4) Sawing The ingot is cut into required lengths on a sawing machine.

[0032] (5) Heating The ingot is heated by a walking beam heating furnace at a temperature of 800-950°C.

[0033] (6) Hot rolling The ingot is hot rolled on the hot rolling equipment, the total processing rate of the hot rolled strip is ≥90%, and online quenching and cooling are carried out. During the final hot rolling, water is sprayed on the hot rolling roller table for quenching and cooling to obtain the strip.

[0034] (7), milling surface The blank surface and edge milling are performed on a double-sided milling machine. The milling cutter speed is 700-900r / min, the milling speed is 8-20m / min, and there is no peeling, oxidation pits, or sticky chips on the surface.

[0035] (8) Rough rolling The material is processed to the washing thickness, i.e. the thickness before the finished product rolling, on a four-high reversing cold rolling mill.

[0036] (9) Edge trimming The edges of the strip after rough rolling are sheared on the shearing equipment to facilitate subsequent finishing.

[0037] (10) Heat treatment annealing Annealing is performed horizontally in a bell-type furnace at a temperature of 280-380°C for 6-10 hours. Under the action of high temperature for a long time, the solid solution strengthening phase formed by rapid cooling after high-temperature rolling in the hot rolling process precipitates and stays on the grain boundary. The second phase of the copper matrix is ​​reduced and the purity is increased, thereby increasing the overall conductivity of the material.

[0038] (11) Cleaning Use sulfuric acid with an acid concentration of 15-20% to clean the surface oxide scale, and the passivation solution is 3-5‰ JHDH-2 for surface passivation treatment. The passivation working temperature is maintained at 60-70℃.

[0039] (12) Finished product rolling The material is rolled from wash stock thickness to finished product thickness on a four-high rolling mill.

[0040] (13) Finished product cleaning Use alkali solution and water to wash away the rolling oil on the surface of the material, and use a passivator to form an extremely thin passivation layer on the surface of the material to isolate the air and prevent the material from oxidation; take finished product thickness samples to test the mechanical properties and conductive properties of the material.

[0041] (14) Finished product cutting Use longitudinal shears to remove the head, tail and edges of the material and cut the material to the finished width; (15) Packaging and storage The finished copper strips are packaged and put into storage after passing the inspection.

[0042] Example 1 A method for improving the electrical conductivity of a high-phosphorus copper alloy strip comprises the following steps: (1) Ingredients: Copper Cu 99.969%, phosphorus P 0.028%; iron Fe 0.0023%; bismuth Bi ≤ 0.001%; ​​antimony Sb ≤ 0.001%; ​​arsenic As ≤ 0.001%; ​​lead Pb ≤ 0.001%; ​​sulfur S ≤ 0.001%; ​​standard cathode copper with this specific composition and the returned waste materials in the processing of standard cathode copper are used as raw materials; (2) Melting: After weighing the metals, mix them, add charcoal, graphite powder or graphite blocks, fill the furnace with nitrogen or argon to melt the metals into a molten liquid at 1120°C; sample the molten liquid and analyze the content of the controlled components and the results of impurity control; in order to ensure the quality of the melt, the raw materials and covering agents used must be dry; during the melting process, the inert gas filled into the furnace can facilitate the precipitation of gas in the melt, ensuring that the gas content in the melt is low; after melting, let it stand for a period of time, which is conducive to the floating of some oxides, sulfides and carbides. After floating, remove the slag and purify the melt; after the melt is prepared, adjust the composition according to the sampling and analysis results; according to the burn-out of the elements, add necessary trace elements to ensure the qualified composition; (3) Casting: When the composition is confirmed to be within the target range, casting begins. When the copper liquid flows into the crystallizer through the launder to the casting pipe for casting, in order to prevent the elements in the melt in the launder from oxidizing, it can be covered with charcoal or graphite particles and protected with inert gas; or the launder can be designed as a sealed structure and the length of the launder can be shortened. Semi-continuous casting can help ensure the quality of the ingot. Vibration casting can be used in the casting process, which is conducive to the slag in the crystallizer floating up without entering the ingot. During casting, an appropriate amount of borax, carbon black or protective gas is used to cover the melt in the crystallizer. Casting speed: 4.0m / h; Cooling water flow: 1200l / min; Casting can be stopped when the ingot length required for the strip is reached; Ingot specifications: 210*620*5000mm; (4) Sawing: sawing the ingot to the required length on a sawing machine; (5) Heating: The ingot is heated by a walking beam heating furnace at a heating temperature of 800°C; (6) Hot rolling: Ingots are hot rolled on hot rolling equipment, with the total processing rate of hot rolled strip being ≥90%. Online quenching and cooling are implemented, and water is sprayed on the hot rolling rollers for quenching and cooling during the final hot rolling. (7) Milling: Milling the surface and edges of the blank on a double-sided milling machine; (8) Rough rolling: The material is processed to the washing thickness on a four-roll reversing cold rolling mill, that is, the thickness before the finished product is rolled; (9) Edge trimming: The edges of the strips with washed thickness are trimmed on the shearing equipment to facilitate subsequent finishing; (10) Heat treatment annealing: annealing in a bell-type furnace at 380°C for 6 hours, with 75% hydrogen plus 25% nitrogen atmosphere for protection during annealing. (11) Cleaning: Use sulfuric acid with an acid concentration of 15% to clean the surface oxide scale, and the passivation solution is 3‰ JHDH-2 for surface passivation treatment. The passivation working temperature is maintained at 60°C; (12) Finished product rolling: The material is rolled from the wash stock thickness to the finished product thickness on a four-roll rolling mill; (13) Finished product cleaning: Use alkali solution and water to wash away the rolling oil on the surface of the material, and use a passivator to form an extremely thin passivation layer on the surface of the material to isolate the air and prevent the material from oxidation; take finished product thickness samples to test the mechanical properties and electrical conductivity of the material; the electrical conductivity of the material is 84.12% IACS; (14) Finished product shearing: Use longitudinal shearing to remove the head, tail and edges of the material and cut the material to the finished product width; (15) Packaging and warehousing: The finished copper strips are packaged and stored after passing the inspection.

[0043] Example 2 A method for improving the electrical conductivity of a high-phosphorus copper alloy strip comprises the following steps: (1) Ingredients: Cu 99.962%, phosphorus P 0.025%; iron Fe 0.0026%; bismuth Bi ≤ 0.001%; ​​antimony Sb ≤ 0.001%; ​​arsenic As ≤ 0.001%; ​​lead Pb ≤ 0.001%; ​​sulfur S ≤ 0.001%; ​​standard cathode copper with this specific composition and the returned waste materials in the processing of standard cathode copper are used as raw materials; (2) Melting: After weighing the metals, mix them, add charcoal, graphite powder or graphite blocks, fill the furnace with nitrogen or argon to melt the metals into a molten liquid at 1280°C; sample the molten liquid and analyze the content of the controlled components and the results of impurity control; in order to ensure the quality of the melt, the raw materials and covering agents used must be dry; during the melting process, the inert gas filled into the furnace can facilitate the precipitation of gas in the melt, ensuring that the gas content in the melt is low; after melting, let it stand for a period of time, which is conducive to the floating of some oxides, sulfides and carbides. After floating, remove the slag and purify the melt; after the melt is prepared, adjust the composition according to the sampling and analysis results; according to the burn-out of the elements, add necessary trace elements to ensure the qualified composition; (3) Casting: When the composition is confirmed to be within the target range, casting begins. When the copper liquid flows into the crystallizer through the launder to the casting pipe for casting, in order to prevent the elements in the melt in the launder from oxidizing, it can be covered with charcoal or graphite particles and protected with inert gas; or the launder can be designed as a sealed structure and the length of the launder can be shortened. Semi-continuous casting can help ensure the quality of the ingot. Vibration casting can be used in the casting process, which is conducive to the slag in the crystallizer floating up without entering the ingot. During casting, an appropriate amount of borax, carbon black or protective gas is used to cover the melt in the crystallizer. The casting speed is 10.0m / h; the cooling water flow rate is 300l / min; the casting can be stopped when the ingot length required for the strip is reached; ingot specifications: 210*620*5000mm; (4) Sawing: sawing the ingot to the required length on a sawing machine; (5) Heating: The ingot is heated by a walking beam heating furnace at a heating temperature of 950°C; (6) Hot rolling: Ingots are hot rolled on hot rolling equipment, with the total processing rate of hot rolled strip being ≥90%. Online quenching and cooling are implemented, and water is sprayed on the hot rolling rollers for quenching and cooling during the final hot rolling. (7) Milling: Milling the surface and edges of the blank on a double-sided milling machine; (8) Rough rolling: The material is processed to the washing thickness on a four-roll reversing cold rolling mill, that is, the thickness before the finished product is rolled; (9) Edge trimming: The edges of the strips with washed thickness are trimmed on the shearing equipment to facilitate subsequent finishing; (10) Heat treatment annealing: annealing in a bell-type furnace at 320°C for 8 hours, with 75% hydrogen plus 25% nitrogen atmosphere for protection during annealing. (11) Cleaning: Use sulfuric acid with an acid concentration of 20% to clean the surface oxide scale, and the passivation solution is 5‰ JHDH-2 for surface passivation treatment. The passivation working temperature is maintained at 70°C; (12) Finished product rolling: The material is rolled from the wash stock thickness to the finished product thickness on a four-roll rolling mill; (13) Finished product cleaning: Use alkali solution and water to wash away the rolling oil on the surface of the material, and use a passivator to form an extremely thin passivation layer on the surface of the material to isolate the air and prevent the material from oxidation; take finished product thickness samples to test the mechanical properties and electrical conductivity of the material; the electrical conductivity of the material is 85.14% IACS; (14) Finished product shearing: Use longitudinal shearing to remove the head, tail and edges of the material and cut the material to the finished product width; (15) Packaging and warehousing: The finished copper strips are packaged and stored after passing the inspection.

[0044] Example 3 A method for improving the electrical conductivity of a high-phosphorus copper alloy strip comprises the following steps: (1) Ingredients: Cu 99.961%, phosphorus P 0.021%; iron Fe 0.0025%; bismuth Bi ≤ 0.001%; ​​antimony Sb ≤ 0.001%; ​​arsenic As ≤ 0.001%; ​​lead Pb ≤ 0.001%; ​​sulfur S ≤ 0.001%; ​​standard cathode copper with this specific composition and the returned waste materials in the processing of standard cathode copper are used as raw materials; (2) Melting: After weighing the metals, mix them, add charcoal, graphite powder or graphite blocks, fill the furnace with nitrogen or argon to melt the metals into a molten metal at 1200°C; sample the molten metal and analyze the content of the controlled components and the results of impurity control; in order to ensure the quality of the melt, the raw materials and covering agents used must be dry; during the melting process, the inert gas filled into the furnace can facilitate the precipitation of gas in the melt, ensuring that the gas content in the melt is low; after melting, let it stand for a period of time, which is conducive to the floating of some oxides, sulfides and carbides. After floating, remove the slag and purify the melt; after the melt is prepared, adjust the composition according to the sampling and analysis results; according to the burn-out of the elements, add necessary trace elements to ensure the qualified composition; (3) Casting: When the composition is confirmed to be within the target range, casting begins. When the copper liquid flows into the crystallizer through the launder to the casting pipe for casting, in order to prevent the elements in the melt in the launder from oxidizing, it can be covered with charcoal or graphite particles and protected with inert gas; or the launder can be designed as a sealed structure and the length of the launder can be shortened. Semi-continuous casting can help ensure the quality of the ingot. Vibration casting can be used in the casting process, which is conducive to the slag in the crystallizer floating up without entering the ingot. During casting, an appropriate amount of borax, carbon black or protective gas is used to cover the melt in the crystallizer. The casting speed is 8m / h; the cooling water flow rate is 800l / min; the casting can be stopped when the ingot length required for the strip is reached; ingot specifications: 210*620*5000mm; (4) Sawing: sawing the ingot to the required length on a sawing machine; (5) Heating: The ingot is heated by a walking beam heating furnace at a heating temperature of 900°C; (6) Hot rolling: Ingots are hot rolled on hot rolling equipment, with the total processing rate of hot rolled strip being ≥90%. Online quenching and cooling are implemented, and water is sprayed on the hot rolling rollers for quenching and cooling during the final hot rolling. (7) Milling: Milling the surface and edges of the blank on a double-sided milling machine; (8) Rough rolling: The material is processed to the washing thickness on a four-roll reversing cold rolling mill, that is, the thickness before the finished product is rolled; (9) Edge trimming: The edges of the strips with washed thickness are trimmed on the shearing equipment to facilitate subsequent finishing; (10) Heat treatment annealing: annealing in a bell-type furnace at 280°C for 10 hours, with 75% hydrogen plus 25% nitrogen atmosphere for protection during annealing. (11) Cleaning: Use sulfuric acid with an acid concentration of 18% to clean the surface oxide scale, and the passivation solution is 4‰ JHDH-2 for surface passivation treatment. The passivation working temperature is maintained at 65°C; (12) Finished product rolling: The material is rolled from the wash stock thickness to the finished product thickness on a four-roll rolling mill; (13) Finished product cleaning: Use alkali solution and water to wash away the rolling oil on the surface of the material, and use a passivator to form an extremely thin passivation layer on the surface of the material to isolate the air and prevent the material from oxidation; take finished product thickness samples to test the mechanical properties and electrical conductivity of the material; the electrical conductivity of the material is 87.42% IACS; (14) Finished product shearing: Use longitudinal shearing to remove the head, tail and edges of the material and cut the material to the finished product width; (15) Packaging and warehousing: The finished copper strips are packaged and stored after passing the inspection.

[0045] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Any equivalent changes or modifications made according to the essence of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for improving the electrical conductivity of a phosphor copper alloy strip, characterized in that: It mainly includes batching, smelting, casting, sawing, heating, hot rolling, milling, rough rolling, trimming, heat treatment annealing, cleaning, and finished product finishing steps; Wherein, when mixing the ingredients, by mass percentage, the ingredients of Cu≥99.90%, P 0.02-0.03%, Fe 0.002-0.01%, Bi≤0.001%, Sb≤0.002%, As≤0.002%, Pb≤0.005%, and S≤0.005% are used for mixing; During heat treatment annealing, place it flat in a bell-type annealing furnace and anneal at 280-380°C for 6-10 hours.

2. A method for improving the electrical conductivity of a phosphorus copper alloy strip according to claim 1, characterized in that: The total mass percentage of Bi, Sb, As, Pb and S shall not exceed 0.03%.

3. The method for improving the electrical conductivity of a phosphor copper alloy strip according to claim 1, characterized in that: The P element is added in the form of copper-phosphorus alloy, and the Fe element is added in the form of iron flakes.

4. The method for improving the electrical conductivity of a phosphorus copper alloy strip according to claim 1, characterized in that: During smelting, the prepared raw materials are put into the smelting furnace and covered with a mixture of graphite powder and dehydrated charcoal. The smelting temperature is 1120~1280℃. After smelting, the raw materials are allowed to stand to facilitate the floating of the slag of oxides, sulfides and carbides in the melt. The floating slag is removed to purify the melt.

5. A method for improving the electrical conductivity of a phosphor-copper alloy strip according to claim 4, characterized in that: A semi-continuous casting machine is used for vibration casting to obtain an ingot, the casting speed is 4.0-10.0 m / h, the cooling water flow rate is 300-1200 l / min, and an appropriate amount of borax or carbon black is used to cover the melt in the crystallizer during casting.

6. A method for improving the electrical conductivity of a phosphor copper alloy strip according to claim 5, characterized in that: Before hot rolling, the ingot is heated in a walking beam heating furnace at a heating temperature of 800-950°C.

7. A method for improving the electrical conductivity of a phosphor copper alloy strip according to claim 6, characterized in that: The ingot is hot rolled on the hot rolling equipment, the total processing rate of the hot rolled strip is ≥90%, online quenching and cooling is implemented, and water spray quenching and cooling are carried out on the hot rolling roller during the final hot rolling.

8. The method for improving the electrical conductivity of a phosphor copper alloy strip according to claim 1, characterized in that: The electrical conductivity of the phosphor copper alloy strip is greater than 83% IACS.